PP.06.08: VALIDATION OF A NEW PIEZO-ELECTRONIC DEVICE FOR NON-INVASIVE MEASUREMENT OF ARTERIAL PULSE WAVE VELOCITY. (June 2015) - Morales, M.; Cuffaro, P.; Barochiner, J.; Rada, M.; Alfie, J.; Aparicio, L.; Marin, M.; Galarza, C.; Waisman, G.
Abstract : Objective: our aim was to validate a new device for pulse velocity(PWC) measurement-Aortic- according to the recommendations of the Artery Society and using SphygmoCor as the comparator device.. Design and method: 85 subjects 18–80 years-old from both sexes were included, divided into 3 age groups: < 30, 30–60 and > 60 years (minimun of 25 individuals per group) and with an equal number of hypertensive and normotensive subjects per group. Weight, height, blood pressure (BP) and PWV were assesed, performing 6 PWV determinants per subject: 3 with Aortic and 3 with SphygmoCor, in an alternative fashion. The Bland-Altman method was used to establish the level of agreement between the two devices.. Results: PWV was 6.96 (±1.84) and 7 (±1.54) m/s with Aortic and SphygmoCor, respectively, showing a high correlation: r = 0.89, p < 0.001. The coefficient of repeatability was 16.87 for Aortic and 4.22 for SphygmoCor. Applying the Bland-Altman method, the mean difference between devices was 0.02 (±0.84) m/s, which is considered an excellent level of agreement. Of the study population, 75.3% (n = 64), 15.3% (n = 13) and 9.4% (n = 8) reached an excellent (mean difference <  = 0.5 ± 0.8 m/s), acceptable (mean difference <  = 1.0 ± 1.5 m/s) and poor (mean difference >  = 1.0 ± 1.5 m/s) level of agreement, respectively. Conclusions: Aortic showed an excellent level of agreement with SphygmoCor, the reference method, according to the Artery Society recommendations for PWV measurement.